Observation of Diastereomeric Interconversions of β‐Sulfinylsubporphyrins as Evidence for Bowl Inversion. Issue 33 (11th June 2015) - Yoshida, Kota; Osuka, Atsuhiro
Abstract B‐Methoxy β‐(4‐methoxyphenylsulfinyl)subporphyrin and B‐phenyl β‐(4‐methoxyphenylsulfinyl)subporphyrin were synthesized by oxidation of the corresponding β‐sulfanylsubporphyrins with m‐chloroperbenzoic acid and were separated into diastereomers, respectively. B‐Methoxy subporphyrin diastereomers were interconverted to each other in methanol or ethanol, whereas such interconversion was not observed for B‐phenyl subporphyrin diastereomers even at high temperature. Diastereomeric interconversions of B‐methoxy subporphyrins were dramatically accelerated by addition of trifluoroacetic acid. These results suggest that the diastereomeric interconversions of B‐methoxy subporphyrins, namely, their bowl inversions, proceed via a mechanism involving protonation‐induced generation of subporphyrin borenium cations followed by nucleophilic attacks by alcohols.